Impact of Future Work Self on Employee Workplace Wellbeing: A Self-Determination Perspective - Li, Zhongqiu; Yang, Yang; Zhang, Xue; Lyu, Zhuo (Frontiers in Psychology, 2021)
In this study, we examine the association between future work self and employee’s workplace well-being by proposing a moderated mediation model. Based on self-determination theory, self-management is identified as the mediator, and person–organisation fit is identified as the moderator in this study. We collected two waves data from of 239 Chinese employees. Analysis results show future work self were related to greater employee’s workplace well-being, and self-management mediates the links between both. We also find that the person–organisation fit strengthens the positive relationship between future work self and self-management, as well as the indirect effect of future work self on employee’s workplace well-being via self-management. The findings of the study extend the antecedents of employee’s workplace well-being, highlight the importance of future work self about current work-related output.